The efficacy of group counselling on perceived stress among infertile women undergoing in vitro fertilization treatment: An RCT - Zeinab Hamzehgardeshi; Fereshteh Yazdani; Forouzan Elyasi; Mahmood Moosazadeh; Sepideh Peyvandi; Keshvar Samadaee Gelehkolaee; Maryam Shahidi (Shahid Sadoughi University of Medical Sciences, 2019)
Background One of the stressful and critical experiences that threat the individual, family, marital, and social stability is infertility. Objective To identify the effects of midwifery-led counselling programs on the perceived stress of the women undergoing assisted reproductive treatment. Materials and Methods In this randomized clinical trial, 50 infertile women who underwent in vitro fertilization treatment for the first time were enrolled in two groups. The intervention group received six sessions of group counselling by M.Sc. midwifery of counseling student and the control group received only the routine care. All participants filled Newton's standard questionnaire before and at the time of puncture, embryo transfer and the pregnancy test. Results The mean ± SD scores for the perceived infertility stress before the intervention in the control and the intervention groups were 167.92 ± 12.14 and 166.75 ± 13.27, respectively. The mean of perceived stress after intervention at the time of oocyte puncture in the control and case group were 177.12 ± 19.37 and 115.75 ± 13.88, at the time of embryo transfer were 179.40 ± 18.34 and 118.08 ± 15.37, and at the time of pregnancy test was 183.76 ± 14.97 and 120.50 ± 16.24, respectively. The perceived stress of infertility after intervention were statistically significant in the two group (p ≤ 0.001). Conclusion Group counselling is one of the effective methods for reducing the perceived stress in the women undergoing assisted reproductive treatment.